Multilevel programming model for constructing schedules processing requirements of different types of sets (in the formation of groups of parties) - Кротов, К. В.; Шишкевич, В. Е. (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
In the paper, the multi-level programming model for efficient composition of the groups of parties, scheduling of operations with the processing of claims included in the kits of different types, with restrictions on the duration of the intervals of the system.